2015
DOI: 10.1111/ldrp.12088
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Attributes, Attention, and Self‐Efficacy of Adequate and Inadequate Responders in a Fourth Grade Reading Intervention

Abstract: We examined cognitive attributes, attention, and self-efficacy of fourth grade struggling readers who were identified as adequate responders (n = 27), inadequate responders with comprehension only deficits (n = 46), and inadequate responders with comprehension and word reading deficits (n = 52) after receiving a multicomponent reading intervention. We also included typical readers (n = 40). These four groups were compared on measures of nonverbal reasoning, working memory, verbal knowledge, listening comprehen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
44
1

Year Published

2016
2016
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(47 citation statements)
references
References 85 publications
(135 reference statements)
2
44
1
Order By: Relevance
“…Children with high self-efficacy benefited from the intervention more than the control group in word reading fluency, whereas children with low selfefficacy benefited from the intervention less than the control group in spelling. The first finding is in accordance with the previous studies which suggest that high self-efficacy is related to better reading skills (Carroll & Fox, 2017;Lee & Zentall, 2012;Peura et al, 2019) and can positively predict children's response to a reading intervention (Cho et al, 2015). However, it was somewhat unexpected that GL Reading players with poor self-efficacy developed less than the control group in spelling.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Children with high self-efficacy benefited from the intervention more than the control group in word reading fluency, whereas children with low selfefficacy benefited from the intervention less than the control group in spelling. The first finding is in accordance with the previous studies which suggest that high self-efficacy is related to better reading skills (Carroll & Fox, 2017;Lee & Zentall, 2012;Peura et al, 2019) and can positively predict children's response to a reading intervention (Cho et al, 2015). However, it was somewhat unexpected that GL Reading players with poor self-efficacy developed less than the control group in spelling.…”
Section: Discussionsupporting
confidence: 90%
“…Self-efficacy may also affect how children respond to reading interventions, possibly because children with high self-efficacy are more persistent and willing to try than children with low self-efficacy (Cho, Roberts, Capin, & Roberts, 2015).…”
Section: Self-efficacy and Game-based Learningmentioning
confidence: 99%
“…This is especially true for students who do not respond adequately to reading interventions. Research aimed at understanding the cognitive attributes of these low responders (e.g., Cho et al, 2015; Miciak et al, 2014) and determining how best to address their severe and seemingly unyielding reading difficulties (e.g., Pyle & Vaughn, 2012) is currently on the frontier of reading intervention research. More individualized interventions, like those tested in earlier decades, might hold clues for contemporary researchers seeking to understand how to help students who benefit little from a standardized approach.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, self-efficacy can influence a struggling reader's application of learned reading skills and strategies. Upon receiving reading intervention, Cho et al (2015) found the reading outcomes of students with low reading comprehension yet higher self-efficacies were more likely to improve than students with lower self-efficacies.…”
Section: Introductionmentioning
confidence: 99%
“…Instruction in reading subskills is merited and supported by research (Scammaca, Roberts, Vaughn & Stuebing, 2015;Wanzek, Wexler, Vaughn, & Ciullo, 2010) yet too often is the predominant form of reading instruction received by struggling readers (Allington, 1983). Struggling readers with low self-efficacy often doubt their reading skills can be improved (Cho et al, 2015. ) Thus, struggling readers require a more balanced approach to literacy instruction to develop, hone, and successfully apply their reading skills within the context of authentic literacy.…”
Section: Introductionmentioning
confidence: 99%